Rain Monitoring System for Nutmeg Drying Based on Internet of Things - Dirja Nur Ilham; Eri Satria; Fera Anugreni; Rudi Arif Candra; Herma Nugroho Rono Adi Kusumo (Journal of Computer Networks, Architecture and High Performance Computing, 2021)
One of the stages in drying the nutmeg is drying the nutmeg in the afternoon which is directly illuminated by the sun. The nutmeg owners in South Aceh is very difficult to get information about rain falling during the day if they are outside or are not in the nutmeg drying area. The process of monitoring the occurrence of rain during the drying of the nutmeg has been done manually by monitoring or seeing the state of the sky when it is cloudy. The purpose of this research is to create a rain monitoring system based on the “Internet of things” internet to make it easier for nutmeg owners to get information about rain falling from a distance. This research uses nodeMCU which functions as a controller of a rain monitoring system, a raindrop sensor as a rain detection sensor. The working system of the rain monitoring tool is by connecting the nodeMCU to the led light and if the raindrop sensor is exposed to rain then the led light will turn on or light up and the raindrop sensor reads the data point. If the data point is read 1024, it indicates that the condition is not raining, while if the data point value is 700 -1023, it indicates the condition of the drizzle, and the data point value from 0-600 indicates the heavy rain condition. The raindrop sensor sends data points to the ThingsIO.AI website as a condition notification that the nutmeg drying area is drizzling, heavy rain, or no rain. For monitoring of nutmeg drying area, it can be accessed remotely via the “website ThingsIO.AI” using smartphones and computers that are connected by the internet. Based on the results of testing the average data point delivery time is 1 minute and the value of the data point obtained is 488-1009